A classification of complications in urogynecology - Gałczyński, Krzysztof; Futyma, Konrad; Rechberger, Tomasz (Menopause Review/Przegląd Menopauzalny, 2014)
The frequency of female pelvic floor reconstruction surgery with synthetic materials has been systematically rising for the last 30 years. Nowadays, they are widely used in urogynecology with a high cure rate, and a statistically significant better outcome compared to classical vaginal repair procedures. This type of operation progressed in some areas from an indication for recurrent prolapse to that of using them in primary procedures. Nevertheless, implantation of synthetic material is associated with the occurrence of specific complications and side-effects. The number and type of complications varies, depending on the study, reaching as much as 10% in some centers. The International Continence Society (ICS) and International Urogynecological Association (IUGA) have introduced an interesting tool for the evaluation of complications related directly to the insertion of prostheses and grafts in the female pelvic floor. The purpose of this classification is to describe possible complications with numbers and letters which together form a code containing comprehensive information about the complication. This article presents the clinical and practical aspects of this classification and first comments about its usability. The presented classification may serve as a tool for the development of national and international registries of urogynecological procedures that would be a great source of information on the number and type of operations performed, their effectiveness and potential complications.